Controllable Activation of Pd‐G3 Palladacycle Precatalyst in the Presence of Thiosugars: Rapid Access to 1‐Aminobiphenyl Thioglycoside Atropoisomers at Room Temperature. Issue 24 (21st November 2017) - AL‐Shuaeeb, Riyadh Ahmed Atto; Dejean, Camille; Alami, Mouâd; Messaoudi, Samir
Abstract: A controllable method for the functionalization of XantPhos Pd‐G3 precatalyst with thiosugars and thiols has been established. Under mild and operationally simple reaction conditions through just mixing of precatalyst and thiosugars (α‐ or β‐mono‐, di‐ and poly‐thiosugar derivatives) in water at 25 °C for 20 min, a series of 1‐aminobiphenyl thioglycosides that are difficult to synthesize by classical methods has been synthesized in very high yields. Abstract : Pour some thiosugar on me : Activation of XantPhos Pd‐G3 precatalyst with thiosugars and thiols under mild and operationally simple reaction conditions is reported. A series of 1‐aminobiphenyl thioglycosides has been synthesized in very high yields.